Study of Thermal Effect on The Weld Bead Geometry During Fusion Welding - Sabeeh Abed-Alkareem, Salah (Journal of Engineering and Sustainable Development, 2013)
This work aims basically to study the thermal effect caused by the weldment surface temperature and welding speed on the main features of weld geometry (bead width and penetration) during fusion welding (GMAW) type TIG for hot rolled low carbon steel type AISI 1025 sheets with 4 mm thickness. Design of Experiment (DOE) with Response Surface Methodology (RSM) is used to predict the influence of these input parameters on the weld bead width and penetration. Mathematical models for the responses are obtained in terms of these welding parameters. Statistical analyses of Variance (ANOVA) are also utilized to verify the adequacy of these models. The results of these quadratic models indicated that both weld bead width and penetration increase with increasing the weldment surface temperature and welding speed. In order to reach the optimum bead width and penetration, numerical optimization is achieved for obtaining a better shape of the weld bead geometry. A good agreement is found between the results of these models and optimization with experimental data at a confidence level of more than 90%. Keywords: Temperature, Welding Speed, Fusion Welding, Bead geometry, Modeling, ANOVA.